The influence of Chinese trade policy on automobile assembly and parts - Deborah L. Swenson (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper analyzes the economic effects of content-based import tariffs China imposed on imported auto parts. While China's policy penalized any firm that assembled cars with less than 60 percent Chinese content, the policy was most likely to affect foreign affiliated firms who were more likely to exceed the content ceiling. To assess whether foreign-affiliated firms differentially changed their input sourcing this paper uses Chinese product trade data for 1997 to 2009 which report trade transactions by firm ownership type. Compared with import transactions for other firms, the data show that foreign-affiliated firms appear to have mitigated the effects of the policy by reducing import transaction prices, and by reducing their import quantities on the extensive margin. While China's content-based auto import trade policy was repealed in 2009 after China lost its dispute case at the WTO, the extraordinary growth in China's global export of auto parts since 2005 suggests that China's short term trade policy may have contributed to enduring effects in global supply chains.
Keywords: F10; F14; F20; 330; content-based tariff policy; imported intermediate inputs